The Influence of Personality and Emotional Intelligence on Burnout and Its Implications for Employee Performance at PT Cirebon Hotel - Difani Nazwa Fadilah; Kartono Kartono (Interdisciplinary Social Studies, 2026)
This study aims to investigate the influence of personality and emotional intelligence on burnout and its implications for employee performance at PT Cirebon Hotel and Convention (The Luxton Cirebon). The research is grounded in the high emotional pressure and job demands characteristic of the hospitality sector, which can contribute to burnout and diminish employee performance. The methodology employed is a quantitative approach with a causal-associative design. The population of this study consists of 250 employees, with a sample of 154 respondents determined using the Slovin formula. Data were collected through a questionnaire employing a Likert scale and subsequently analyzed using path analysis with SPSS software. The findings indicate that personality and emotional intelligence exert a significant negative influence on burnout. Furthermore, personality and emotional intelligence contribute significantly and positively to employee performance, while burnout exerts a significant negative effect on performance. This study also reveals that burnout functions as a mediating variable in the relationship between personality and emotional intelligence and employee performance. The results of this study offer a theoretical contribution to the development of organizational behavior research, as well as practical implications for hotel management in achieving sustainable human resource management.